“ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN” (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2013-2015) - Wahidatul Hasanah; Mohammad Amin; Muhammad Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2017)
ABSTRACTThis study aimed to analyze the effect of DER (Debt to Equity Ratio), ROA (Return on Asset), and FirmSize to Firm Value (study on the manufacturing companies listed on the Indonesia stock exchange period 2013-2015). The population on this research is all the manufacturing companies listed on Indonesia Stock Exchangeon period from 2013-2015. The samples used were 58 manufacturing companies. The Samples of this researchis based on purposive sampling, means that the samples were taken by certain criteria. the analytical methodused on this research is multiple regression analysis, F-test and T-test. The result on this research showing thatvariable DER, ROA, and firm Size have significantly influence to variable Firm value.Keyword : Debt to Equity ratio, Return On Asset, Firm Size, Firm Value